2007
DOI: 10.1007/s00240-007-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of primary hyperparathyroidism with and without kidney stones

Abstract: The exact metabolic-physiological background for kidney stone formation in primary hyperparathyroidism (PHPT) is unclear. To obtain clarification, this retrospective data analysis was conducted in 131 patients with PHPT who had undergone a detailed ambulatory evaluation on a random diet since 1980. The baseline biochemical presentation of 78 patients with PHPT with stones was compared with that of 53 patients without stones. Compared to those without stones, the stone-forming patients had a more marked hyperca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
1
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 16 publications
2
39
1
9
Order By: Relevance
“…This is in contrast to the findings of Odvina et al (17) who reported a frequency of 60% found by a history of passing stone, removal of stone or roentgenogram. They retrieved data from 131 patients aged R18 years and diagnosed with PHPT by hypercalcaemia, high PTH levels and no secondary cause of hyperparathyroidism.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is in contrast to the findings of Odvina et al (17) who reported a frequency of 60% found by a history of passing stone, removal of stone or roentgenogram. They retrieved data from 131 patients aged R18 years and diagnosed with PHPT by hypercalcaemia, high PTH levels and no secondary cause of hyperparathyroidism.…”
Section: Discussioncontrasting
confidence: 99%
“…This may suggest that a CT scan in a cross-sectional setting is more sensitive than sonography in the diagnosis of nephrocalcinosis and should be used for the routine examination of the patients. It is difficult to conclude on the prevalence of renal stones in PHPT as the reports vary from 7% (18) to 60% (17). The wide range in reported prevalence of stones is difficult to explain but may be based on the differences between studies in study populations, assessment of previous clinical stones and methodology used to identify calcifications and persistent stones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney stones that are generally related to hypercalciuria are a common complication in PHPT patients (9). Nonconservative Arg990Gly polymorphism (SNP) of the CASR gene is associated with a specific phenotype in PHPT patients, characterized by kidney stones, lower serum concentrations of PTH, and higher urine calcium excretion (10,11).…”
Section: Introductionmentioning
confidence: 99%